Genomic epidemiology of carbapenemase-producing Gram-negative bacteria at the human-animal-environment interface in Djibouti city, Djibouti - Mohamed, Hasna Saïd; Galal, Lokman; Hayer, Juliette; Benavides, Julio A.; Bañuls, Anne-Laure; Dupont, Chloé; Conquet, Guilhem; Carrière, Christian; Dumont, Yann; Didelot, Marie-Noëlle; Michon, Anne-Laure; Jean-Pierre, Hélène; et al. (The Science of the total environment, 2023)
The emergence of carbapenem resistance is a major public health threat in sub-Saharan Africa but remains poorly understood, particularly at the human-animal-environment interface. This study provides the first One Health-based study on the epidemiology of Carbapenemase-Producing Gram-Negative Bacteria (CP-GNB) in Djibouti City, Djibouti, East Africa. In total, 800 community urine samples and 500 hospital specimens from humans, 270 livestock fecal samples, 60 fish samples, and 20 water samples were collected and tested for carbapenem resistance. The overall estimated CP-GNB prevalence was 1.9 % (32/1650 samples) and specifically concerned 0.3 % of community urine samples, 2.8 % of clinical specimens, 2.6 % of livestock fecal samples, 11.7 % of fish samples, and 10 % of water samples. The 32 CP-GNB included 19 Escherichia coli, seven Acinetobacter baumannii, five Klebsiella pneumoniae, and one Proteus mirabilis isolate. Short-read (Illumina) and long-read (Nanopore) genome sequencing revealed that carbapenem resistance was mainly associated with chromosomal carriage of blaNDM-1, blaOXA-23, blaOXA-48, blaOXA-66, and blaOXA-69 in A. baumannii, and with plasmid carriage in Enterobacterales (blaNDM-1 and blaOXA-181 in E. coli, blaNDM-1, blaNDM-5 and blaOXA-48 in K. pneumoniae, and blaNDM-1 in P. mirabilis). Moreover, 17/32 CP-GNB isolates belonged to three epidemic clones: (1) A. baumannii sequence type (ST) 1697,2535 that showed a distribution pattern consistent with intra- and inter-hospital dissemination; (2) E. coli ST10 that circulated at the human-animal-environment interface; and (3) K. pneumoniae ST147 that circulated at the human-environment interface. Horizontal exchanges probably contributed to carbapenem resistance dissemination in the city, especially the blaOXA-181-carrying ColKP3-IncX3 hybrid plasmid that was found in E. coli isolates belonging to different STs. Our study highlights that despite a relatively low CP-GNB prevalence in Djibouti City, plasmids harboring carbapenem resistance circulate in humans, animals and environment. Our findings stress the need to implement preventive and control measures for reducing the circulation of this potentially emerging public health threat. [Display omitted] •Carbapenem resistance epidemiology is poorly understood in sub-Saharan Africa.•Carbapenem resistance is present in Djibouti City, Djibouti.•Genomic analyses highlighted its frequent intra- and inter-hospital dissemination.•It also circulates across the human-animal-environment interface.